Schwartz Rounds in Higher Education Settings: A Systematic Review of the Research with Recommendations - Amy Zile; Joel Owen; Hugh Gorick; Amy Orford; Georgia Panagiotaki (Journal of Medical Education and Curricular Development)
BACKGROUND Higher education institutions (HEIs) have recently integrated Schwartz Rounds (Rounds) as innovative ways of supporting health professional students’ reflective practice, interprofessional learning and compassionate care. Emerging evidence suggests that Rounds benefit students’ shared sense of belonging and insight into emotional aspects of training and care, providing safe places to share experiences and reflect. Our review examines the current literature regarding health students’ evaluation of Rounds in HEIs, exploring experiences and perceived benefits of participating. We consider methodological issues with the existing literature and propose ways of addressing these in future research. METHODS Systematic searches were conducted on EBSCO, PsycINFO, PubMed and ASSIA to identify available literature relating to Schwartz Rounds in higher education. Eight studies – six with a mixed method design and two qualitative – were included in the review. Study quality and risk of bias were assessed. Evaluation survey data and themes generated from qualitative responses were considered together and a narrative synthesis was constructed. RESULTS Despite challenges with differing measurements and scale usage, five themes were identified reflecting the experience and perceived benefits for students attending Rounds. Students highlighted the value of peer connection and communication; normalisation of emotions; collaborative reflection and self-awareness; and the relevance of Rounds in their daily work and patient care. Students also commented on barriers to participation including Rounds’ multidisciplinary nature, their group size, and the presence of staff. The majority of students rated Rounds as excellent or exceptional and agreed they should be integrated into the curriculum. CONCLUSIONS Our findings on Schwartz Rounds in higher education suggest they support student reflective practice and confidence in providing compassionate, high-quality patient care. However, the quality of research in this area is mixed, reflecting the relatively recent integration of Rounds in Higher education, and the challenges of implementing and evaluating new interventions in educational settings.